Determining quality parameters of alcohol-free functional beverage by the procedure that employs affine transformations - Zhulinska, Oksana; Svidlo, Karyna (Technology audit and production reserves, 2017)
The subject of present research is to determine AFB quality indicators according to a procedure that uses affine transformations, which could be applied at any ideal value. The application of this procedure provides FFP with the most accurate quality indicators according to the results of the sample. We found numerical characteristics of the given set – mathematical expectation, variance, mean root square deviation, third order central moment, fourth order central moment, asymmetry factor, coefficient of excess. We determined estimates of quality indicators: 1) mass fraction of dry substances – 92.36 %; 2) mass fraction of sediment – 82.65 %; 3) mass fraction of pulp – 91.07 %; 4) mass fraction of titrated acids – 82.93 %; 5) viscosity (dynamic) – 94.20 %; 6) pH – 82.97 %. It was established that the coefficient of variation of random magnitudes and is less than 0.1. This suggests a slight dispersion of these values. The results obtained allow us to solve a number of practical tasks and are used in the method of control over indicators of quality and safety of alcohol-free beverages with functional purpose. Implementation of the procedure for quality evaluation using affine transformations provides FFP with the most accurate quality indicators according to the results of the sample. An analysis of this model and comparison with the previous quality assessment could be applied at any ideal value.